2006
DOI: 10.1016/j.jcrs.2006.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Sedative effect of acupuncture during cataract surgery

Abstract: Acupuncture was effective in reducing anxiety related to cataract surgery under topical anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…Six studies measured heart rate before and after intervention; none of these reported a significant difference between the acupuncture and sham groups [10, 2123, 25, 36]. Two studies also reported no significant difference in blood pressure [17, 23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies measured heart rate before and after intervention; none of these reported a significant difference between the acupuncture and sham groups [10, 2123, 25, 36]. Two studies also reported no significant difference in blood pressure [17, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Two other studies investigated discomfort according to VAS scale ratings (0–100 points) and reported that discomfort was higher in control groups (MD = −12.08, P < .00001, 95% CI [−14.2, − 10.13], Figure 6) [21, 22]. …”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, this simple search strategy yielded more trials than the updated review that used complex search strategies aimed at detecting all three groups in one trial. When trials published up to March 2008 were considered, we consequently included seven more acupuncture trials [41][47], two more acupoint stimulation trials [48], [49], and four more TENS trials [37], [50][52] than the previous review.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on traditional point locations to differentiate the exposures resulted in statistically significant differences in four studies [35,44,80,82] but not in studies of migraine [48], chemotherapy induced nausea [54], knee osteoarthritis [61], or for emotional distress or cravings among substance users [69]. Relying on traditional indications of acupuncture points to differentiate the exposures resulted in statistically significant differences in one study [15], but not in studies of migraine [8,19], depression [9], low back pain [13], cataract surgery [23], nausea and vomiting during cesarean [25], or during early pregnancy [27], nor for diabetic peripheral neuritis [37]. Relying on stimulation techniques to differentiate the exposures resulted in statistically significant differences in two studies [53,81], but deep vs. minimal needle insertion led to no statistically significant differences in reduction in migraine [8,19,48], low back pain [13], pregnant women's pelvic pain [51], or knee osteoarthritis [61]; nor did needling compared to moxibustion have a statistically significant difference on outcomes for pain or ''coldness'' [64].…”
Section: Acupuncture Controlsmentioning
confidence: 99%
“…Among 40 studies that compared acupuncture exposures, 21 observed null outcomes and 18 of these (86%) had exposures that relied on traditional acupuncture theories of point locations [38,41,48,52,54,61,69], indications [8,9,13,19,23,25,27,37], or stimulation [8,13,16,19,48,51,61,64].…”
Section: Acupuncture Controlsmentioning
confidence: 99%